2016
DOI: 10.1371/journal.pone.0153524
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Environmental Factors Associated with Inflammatory Bowel Disease in a Southwestern Highland Region of China: A Nested Case-Control Study

Abstract: BackgroundThe aim of this study was to examine environmental factors associated with inflammatory bowel disease (IBD) in Yunnan Province, a southwestern highland region of China.MethodsIn this nested case-control study, newly diagnosed ulcerative colitis (UC) cases in 2 cities in Yunnan Province and Crohn’s disease (CD) cases in 16 cities in Yunnan Province were recruited between 2008 and 2013. Controls were matched by geography, sex and age at a ratio of 1:4. Data were collected using the designed questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…In addition, fresh food and vegetable consumption remains low, and dining out has grown substantially, especially among young singles (KOSIS, http://kosis.kr/). These dietary and lifestyle factors, linked to industrialization, may increase the risk of IBD, particularly for those exposed to these determinants at an early age . However, further studies are needed to assess the changes in IBD incidence to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, fresh food and vegetable consumption remains low, and dining out has grown substantially, especially among young singles (KOSIS, http://kosis.kr/). These dietary and lifestyle factors, linked to industrialization, may increase the risk of IBD, particularly for those exposed to these determinants at an early age . However, further studies are needed to assess the changes in IBD incidence to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…These dietary and lifestyle factors, linked to industrialization, may increase the risk of IBD, particularly for those exposed to these determinants at an early age. 28,29 However, further Epidemiology of IBD in Korea studies are needed to assess the changes in IBD incidence to confirm this hypothesis.…”
Section: Epidemiology Of Ibd In Koreamentioning
confidence: 99%
“…Our findings were also partly similar to those in a case-control study published in 2015, which studied 374 incident IBD cases and 789 neighborhood controls in 8 regions in Asia, which found that former smoking was associated with an increased risk of UC in Asians (aOR [95% CI] 2.0 [1.2–3.4]), while neither current nor former smoking was significantly associated with CD [24]. Two other Chinese studies also found former smoking to be a risk factor for UC [25]. Few Asian studies have examined the impact of smoking on IBD outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The association between smoking and surgery could be influenced by age at diagnosis, disease location, disease behaviour, and/or medications used to treat IBD. Further, ethnic differences may play an additional role on this association, with recent evidence suggesting that the impact of smoking on the development of Crohn’s disease varies across ethnicities [29, 30]. Secondly, selection bias in defining the study populations may have introduced bias in our analyses.…”
Section: Discussionmentioning
confidence: 99%